The Social Aspect of Culture Novels Pulang for Literary Studies - Achmad Yasin (Wanastra: Jurnal Bahasa dan Sastra, 2022)
This study aims to find out the socio-cultural setting of the novel Pulang by Tere Liye. This research is library research so that it is not bound by the place. This research method uses a qualitative descriptive method with analytical techniques. The object of the research used is the novel Pulang by Tere Liye. This research is focused on socio-cultural background research that includes language systems, socio-cultural systems, living livelihood systems, religious systems. The technique of collecting data is done by the way researchers read, understand, determine each intrinsic and extrinsic elements of the novel. The results of this study can be concluded that there are 81 statements are stating a socio-cultural background divided into 10 language systems, 50 socio-cultural systems, 17 living livelihood systems, 4 religious systems. Study the socio-cultural system dominates, this has been proven by the number of statements that refer to the system. The socio-cultural system in this novel refers to the attitudes and behavior of each group of people whose life is governed by customs and rules regarding various kinds of unity in an environment where they live and interact day by day. The relevance between the  novel Pulang and the present life is the low interest in learning, so it is hoped that this novel can be used as a material for studying literature in high school because the contents of the novel that show learning are very important for the future.